Współpraca rolników z przetwórstwem rolno-spożywczym w świetle wyników badań ankietowych - Grzelak, Aleksander (The Cooperation of Farmers with Food Processing Industry in the Light of the Questionnaire Research, 2006)
The main aim of the article is to define common and character of cooperation of farms with food processing industry. One has stated that integration of farmers with food enterprises in Poland is not common and formalized. Besides that there is considerable differentiation in range of forms of cooperation of farms with processing in dependence on profile of a production. Relatively the greatest range of these processes are, in the examined farms, in favour of market of milk and industrial plants, the least in turn in favour of producers of pigs and of cereals. One has also perceived distinct characterization of farms integrated with food processing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 274-281